2021
DOI: 10.1080/13670050.2021.1943304
|View full text |Cite
|
Sign up to set email alerts
|

Home literacy practices that support language and literacy development in bilingual children: a longitudinal case study

Abstract: In the past few decades, literature has consistently suggested that bilingual children are at risk for academic failure due to their limited language skills. However, many of these studies included underprivileged bilingual children, and few of them attempted to disentangle the effects of bilingualism from the effects of socioeconomic status. Critically, it is not clear how the language and literacy skills of bilingual children develop when they benefit from home support. This paper presents the case study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Proficiency in reading one's home language can be transferred to other languages (Dolean, 2022), and the extent to which vocabulary growth in one's home language positively affects vocabulary growth in a second language is emphasised by Pretorius and Stoffelsma (2021:28). This is an extension of Cummins' linguistic interdependence hypothesis, which posits that some firstlanguage skills can be advantageously transferred to the process of learning a second language.…”
Section: Reading Development In the Home Languagementioning
confidence: 99%
“…Proficiency in reading one's home language can be transferred to other languages (Dolean, 2022), and the extent to which vocabulary growth in one's home language positively affects vocabulary growth in a second language is emphasised by Pretorius and Stoffelsma (2021:28). This is an extension of Cummins' linguistic interdependence hypothesis, which posits that some firstlanguage skills can be advantageously transferred to the process of learning a second language.…”
Section: Reading Development In the Home Languagementioning
confidence: 99%
“…Hypothesis 2: Based on the literature review (e.g., Sun et al, 2018a,b;Luo et al, 2021;Dolean, 2022), children from higher-SES families are expected to have better language environment in terms of resources and activities. Children's English language and literacy environment is better than that of Mandarin.…”
Section: The Current Studymentioning
confidence: 99%
“…Previous research found that home literacy, that is, exposure to books and reading in the familiar context, is positively related to early language skills such as expressive and receptive language (Payne et al, 1994;Roberts et al, 2005) and early literacy skills, such as letter knowledge, phonological awareness (Evans et al, 2000;Foy and Mann, 2003;Hood et al, 2008;Stephenson et al, 2008). Some studies also suggested that parents may also foster the development of writing competence (Wollman-Bonilla, 2001;Reutzel et al, 2005;Saint-Laurent and Giasson, 2005;Puranik et al, 2018;Hofslundsengen et al, 2019;Guo et al, 2020). In addition, the Home Literacy Model (Sénéchal and LeFevre, 2002;Sénéchal, 2006;Sénéchal et al, 2017) suggests that parent-child interactions on code-related activities, such as the teaching of reading and spelling (formal activities), are related to reading development.…”
Section: Home Literacy and Home Numeracymentioning
confidence: 99%